The relevance of body composition assessment for the rating of perceived exertion in trained and untrained women and men - Lichti, Julia; Maggioni, Martina Anna; Balcerek, Björn; Becker, Philipp Nils; Labes, Robert; Gunga, Hanns-Christian; Fähling, Michael; Steinach, Mathias (Frontiers in Physiology, 2023)
Introduction Mechanic power output (MPO) and oxygen consumption (VO2) reflect endurance capacity and are often stated relative to body mass (BM) but less often per skeletal muscle mass (SMM). Rating of perceived exertion (RPE) has previously shown conflicting results between sexes at submaximal intensities. Individual body composition, however, largely differs due to sex and training status. It was the aim of this study to evaluate RPE of untrained and trained individuals of both sexes considering body composition and to estimate whether RPE will be improved as a tool to determine endurance capacity. Methods The study included 34 untrained adults (age 26.18 ± 6.34 years, 18 women) and 29 endurance trained (age 27.86 ± 5.19, 14 women) who were measured for body composition (InBody 770, InBody Europe B.V., Germany) and tested on a treadmill (Pulsar, H/P/Cosmos, Germany) for aerobic capacity (Metalyzer 3B, Cortex Biophysik GmbH, Germany) in an all-out exercise test applying the Bruce-protocol. VO2, MPO, heart rate (HR), and RPE were obtained at each exercise stage. VO2 and MPO were calculated per BM and SMM. RPE values were correlated with absolute VO2 and MPO, as well as relative to BM, and SMM. HR values and the parameters’ standardized values served for comparison to standard procedures. Results VO2 and MPO was higher in men compared to women and in trained compared to untrained participants. No differences between groups and sexes exist when VO2 and MPO were calculated per BM. When calculated per SMM, VO2 and MPO indicate opposite results already at low intensity stages of exercise test. RPE values had highest correlation with MPO per SMM (R²=0.8345) compared to absolute MPO (R²=0.7609), or MPO per BM (R²=0.8176). Agreement between RPE and MPO per SMM was greater than between RPE and HR (p=0.008). Conclusion Although RPE represents a subjective value at first glance, it was shown that RPE constitutes a valuable tool to estimate endurance capacity, which can be further enhanced if individual body composition is considered. Furthermore, MPO and VO2 should be considered relative to SMM.